2016
DOI: 10.2214/ajr.15.15972
|View full text |Cite
|
Sign up to set email alerts
|

MDCT Venographic Patterns of Dural Venous Sinus Compromise After Acute Skull Fracture

Abstract: Sinus compromise is common in patients with overlying skull fractures. Sinus compression can be distinguished from DVST on MDCT venography and is likely more prevalent than previously estimated. The fracture site may in part determine the pattern of compromise because fractures involving the transverse sinus-sigmoid sinus complex or multiple dural sinuses seem more likely to be affected by thrombosis than fractures involving the SSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
3
9
0
Order By: Relevance
“…Prior studies have established skull fractures as a risk factor for DVST, [9][10][11]17,26 and the results from our study support this. We show a strong association between skull fractures extending to a dural venous sinus and sinus thrombosis.…”
Section: Traumatic Intrasinus Gas Predicts Dvstsupporting
confidence: 89%
“…Prior studies have established skull fractures as a risk factor for DVST, [9][10][11]17,26 and the results from our study support this. We show a strong association between skull fractures extending to a dural venous sinus and sinus thrombosis.…”
Section: Traumatic Intrasinus Gas Predicts Dvstsupporting
confidence: 89%
“…Rischall et al evaluated CTV interobserver reliability in the setting of TBI and found a strong interobserver reliability among three neuroradiologists (κ = 0.627–0.772; p < 0.0001) ( 26 ). The most common source of disagreement reported was between categories of solely sinus compression and indeterminate thrombosis/compression.…”
Section: Resultsmentioning
confidence: 99%
“…Sporadic reports that CVST can also develop with a delay after TBI were identified. Rischall et al performed follow-up CT venography within 30 days post-trauma in 28/107 patients and noted 2/28 patients with delayed venous thrombosis ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…Early diagnosis of CVT should be in the lists of differential diagnoses whenever encountered in the young patients with unusual severe headache, with clinical arterial stroke and absence of risk factors, with intracranial hypertension or patients with hemorrhagic infarction on NCCT. The most common locations of intracranial dural venous sinuses are superior sagittal sinus followed by transverse sinus and sigmoid sinus as respectively [3] [4] [9].…”
Section: Introductionmentioning
confidence: 99%